2022
DOI: 10.1111/hel.12896
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of vonoprazan‐amoxicillin dual therapy for eradicating Helicobacter pyloriinfection in China: A prospective, randomized clinical pilot study

Abstract: Background Vonoprazan‐amoxicillin (VA) dual therapy has been shown to achieve acceptable cure rates for treatment of Helicobacter pylori(H. pylori) in Japan. Its effectiveness in other regions is unknown. We aimed to explore the efficacy of VA dual therapy as first‐line treatment for H. pyloriinfection in China. Methods This was a single center, prospective, randomized clinical pilot study conducted in China. Treatment naive H. pyloriinfected patients were randomized to receive either low‐ or high‐dose amoxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(79 citation statements)
references
References 28 publications
3
76
0
Order By: Relevance
“…The results showed that the eradication of 7-or 10-day VA dual therapy with bid or tid amoxicillin was below 90%. 36 However, 14-day VA dual therapy showed satisfactory efficacy (eradication rate > 90%) as the first-line treatment for H. pylori infection (our unpublished data). Therefore, it was of great interest to explore the duration, dosage, and frequency of VA dual therapy in other regions.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The results showed that the eradication of 7-or 10-day VA dual therapy with bid or tid amoxicillin was below 90%. 36 However, 14-day VA dual therapy showed satisfactory efficacy (eradication rate > 90%) as the first-line treatment for H. pylori infection (our unpublished data). Therefore, it was of great interest to explore the duration, dosage, and frequency of VA dual therapy in other regions.…”
Section: Discussionmentioning
confidence: 78%
“…In China, we conducted a prospective, randomized clinical pilot study to evaluate the efficacy of VA dual therapy for H. pylori eradication. The results showed that the eradication of 7‐ or 10‐day VA dual therapy with bid or tid amoxicillin was below 90% 36 . However, 14‐day VA dual therapy showed satisfactory efficacy (eradication rate > 90%) as the first‐line treatment for H. pylori infection (our unpublished data).…”
Section: Discussionmentioning
confidence: 81%
“…From January 9, 2021, to October 1, 2021, 119 H. pylori ‐positive patients diagnosed by histology or the 13 C‐urea breath test were enrolled from The First Affiliated Hospital of Nanchang University. The detailed inclusion criteria and exclusion criteria were described previously 19 . These patients showed dyspepsia symptoms or visited for a healthy examination and were not treated with H. pylori eradication previously, PPI and antibiotics within the previous month.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed inclusion criteria and exclusion criteria were described previously. 19 These patients showed dyspepsia symptoms or visited for a healthy examination and were not treated with H. pylori eradication previously, PPI and antibiotics within the previous month. Thirteen H. pylori-negative patients (confirmed by the 13 C-urea breath test) without a history of surgery or other diseases were defined as normal controls, whose saliva samples were collected.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…amoxycillin achieved >90%eradication rate in China. 8 Moreover,dualtherapyfor14 daysachievedcure ofinfectionin83.3%ofpatientswithclarithromycin-resistantstrains in the US and Europe. 9 Dual therapy might be optimised by increasing the frequency of amoxycillin from b.…”
Section: Editorsmentioning
confidence: 99%